2019
DOI: 10.1097/mao.0000000000002120
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation in Pediatric Recipients of Cochlear Implants

Abstract: Objective: To determine factors that influence low-frequency hearing preservation following pediatric cochlear implantation and compare hearing preservation outcomes between 20 and 24 mm depth lateral wall electrodes. Study Design: Retrospective chart review. Setting: Tertiary academic referral center. Patients: Pediatric cochlear implant recipients (under the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Two hundred and eleven subjects were used for the study-L24 (80), S8 (24), S12 (14), 422/522 (47), SRW (6), Flex (19), and SLIM J (21). Of these 211 subjects, 84 were omitted from the modeling analyses due to inadequate data (lack of audiometric test score for either 125, 250, and/or 500 Hz).…”
Section: Patient Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two hundred and eleven subjects were used for the study-L24 (80), S8 (24), S12 (14), 422/522 (47), SRW (6), Flex (19), and SLIM J (21). Of these 211 subjects, 84 were omitted from the modeling analyses due to inadequate data (lack of audiometric test score for either 125, 250, and/or 500 Hz).…”
Section: Patient Demographicsmentioning
confidence: 99%
“…Better preoperative hearing has also been correlated with improved rates of long-term hearing preservation. 9,24 However, other studies have failed to support a correlation between these variables and degree of hearing loss after CI. 4,8,13,[25][26][27][28] A better understanding of how patient factors influence hearing outcomes could lead to improvements in CI candidate selection and provide further direction regarding choice of device type and insertion depth in specific populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of combined electric and acoustic hearing has also been well‐demonstrated in children in whom low‐frequency hearing is preserved. 38 , 39 , 40 In addition, the benefit of the combination of acoustic hearing and a cochlear implant has also been well‐demonstrated with bimodal hearing in which patients with a cochlear implant benefit from a hearing aid in the contralateral, poor hearing ear. 41 , 42 Together these data suggest that auditory processing centers can integrate both electric and acoustic signals for an overall greater benefit for speech perception in both adults and children.…”
Section: Introductionmentioning
confidence: 99%
“…Although not limited to children, Causon et al (39) found that individuals with stable hearing loss (as opposed to progressive loss) had a tendency toward higher rates of hearing preservation, which may in part explain the worse outcomes in children with EVA in our cohort, because EVA is typically associated with progressive loss. On the contrary, Selleck et al (17) did not find that progressive hearing loss was predictive of the ability to preserve hearing. Overall, although rates of hearing preservation may be less predictable than for idiopathic hearing loss, the current evidence suggests that hearing preservation is certainly a possibility in children with EVA, even in cases where a perilymphatic gusher is encountered (38).…”
Section: Discussionmentioning
confidence: 93%